Recent advances in head and neck cancer reconstruction - Yadav, Prabha (Medknow Publications & Media Pvt Ltd, 2014)
Treatment of cancer is race against time! Following radical excision, breathing, speech, mastication and swallowing are hampered. Face is invariably involved. Beside functional normalcy, excellent cosmetic restoration is necessary for patient's life quality. Primary wound healing, quick resumption of adequate oral intake, prompt initiation of chemo-radiotherapy has direct bearing on cure. Primary reconstruction with pedicle or free flap is the choice of treatment in most protocols. Composite defects are requiring bone, muscle and skin restrict choice of donor site and may have shortfalls in aesthetic and functional requirements. To improve further newer, and newer modalities are being developed and used to give best aesthetic and functions. Navigation, use of three-dimensional imaging, stereo lithic model and custom made implant for reconstruction are recommended as they promise improvement in aesthetics. Robotic surgeries allow access for resection of tumours and reconstruction with free flap in deep oropharynx obviating need of doing mandibulotomy. Researchers in stem cell and tissue engineering are looking forward to regenerating tissues and avoid the need of autologous tissue flaps. Desired tissue combination across counter may be available in the future. Excellent immunosuppressant drugs have made it possible to reconstruct composite facial anatomical units with allotransplant in a single surgery, along sensory and motor recovery! Mythological heterogenic head transplant like clone Ganesha, will be a reality in the near future!!